Vegetation community and species association of Castanopsis spp. at its habitat in the remnant forest of Cibodas Botanical Garden, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nurdiana DR, Buot IE Jr. 2021. Vegetation community and species association of Castanopsis spp. at its habitat in the remnant forest of Cibodas Botanical Garden, Indonesia. Biodiversitas 22: 4799-4807. Castanopsis is one of the genera of Fagaceae with a large distribution in Indonesia. The genus can be found easily in Java, Sumatera and Kalimantan. Several studies have found an association between Castanopsis and environmental factors dealing with the diversity, dispersal and propagation. So far, there has been no agreement on how Castanopsis interacts with other species within the same genus in nature, especially in the remnant forest under a fragmented state. The objectives of the study were to determine the vegetation associated with Castanopsis and whether each species of the genus Castanopsis co-occur within the remnant forest? A total of 60 plots have been studied in 3 different sites of the remnant forest. The nested sampling method was used to identify the trees, saplings and seedlings. Sixty-seven total species of trees, 140 species of saplings and 121 species of seedlings in Cibodas Botanical Garden remnant forest were recorded. The diversity index for tree, sapling and seedling were 3.5, 3.9 and 4.1, respectively, while evenness index for tree, sapling and seedling were 0.81, 0.8 and 0.85 respectively. The interspecific association of the genus Castanopsis was restricted to C. javanica x C. tungurrut. They are associated positively at sapling stage with Jaccard index of 0.2. However, at tree stage, there was no association out of the pair, C. javanica x C. tungurrut. Competition within genus Castanopsis occurred in the same habitat, though at a lesser degree which needs to be studied further. Dominance of many pioneer species (Oreocnide integrifolia (Gaudich.) Miq., Ostodes paniculata Blume, Cestrum aurantiacum Lindl. and others) at tree stage had been evident. This implies that the Cibodas remnant forest is still in the process of succession towards a more stable climax state.
Keywords: castanopsis; Cibodas Botanical Garden; Remnant forest; Interspecific association; Cibodas Biosphere Reserve